A secure mHealth application for attention deficit and hyperactivity disorder. Issue 1 (24th June 2019) - Rodríguez‐Pérez, Nayra; Caballero‐Gil, Pino; Rivero‐García, Alexandra; Toledo‐Castro, Josué
Abstract: Nowadays, many people have smartphones, the fact that encourages the development of new tools to address different problems. One of its consequences is the recent growth of mHealth, a term that refers to the practice of medicine based on the use of mobile devices for medical and health purposes. This work describes a new mHealth tool to improve memory and cognitive abilities through gamification and serious games. In particular, a mobile application here is proposed to help children that suffer from attention deficit hyperactivity disorder (ADHD). This application integrates the four profiles involved in this disorder: children, parents, teachers, and medical staff. With it, parents can discover if their children suffer the disorder, and children can improve their cognitive abilities through games of different types. Besides, the security aspect of the proposal is emphasized to highlight its importance in mHealth. Thus, the developed tool includes various cryptographic mechanisms to protect the confidentiality of communications and the authenticity of users and data.